Análisis y cartografía mediante SIG de la susceptibilidad a la formación de dolinas en el entorno de Zaragoza - Lamelas Gracia, Maria Teresa (Geographicalia, 2015)
In the surroundings of Zaragoza, karstification processes are especially intense in covered karst areas where fluvial terraces lie directly on Tertiary evaporites. Since the beginning of Quaternary, these processes have lead to the development of collapse and subsidence dolines with a wide range of sizes, which have significant economic impacts. A regional analysis of this phenomenonis needed for a proper spatial management and to reduce economic impact. Therefore, a probability map of dolines was developed using logistic regressionand geographic information systems (GIS). This paper covers the selection of input data, manipulation of data using the GIS technology, and the use of logistic regression to generate a doline probability map. The primary variable in the doline development in this area is geomorphology, represented by the location of endorheic areas and different terrace levels. Secondary variables are the presenceof irrigation and high water table gradient.